1. The problem statement, all variables and given/known data In my notes I keep stumbling upon this equation: Equation 1: E(X-bar^2) = (σ^2)/n + μ^2 I was wondering why the above equation is true and how it is derived. 3. The attempt at a solution E(X-bar^2) ##Summations are from i/j=1 to n = E[(Σx_i/n)^2)] = E[(Σx_i/n)(Σx_j/n)] =(1/n^2)E[(Σx_i)(Σx_j)] =(1/n^2)ΣΣE(x_i*x_j) =E(x_1^2) + E( x_2^2 + ... + E(x_n^2) + E(x_1*x_2) + E(x_1*x_3) + ... : Equation 2 I'm stuck at this point. Could someone show me how you get to Equation 1 from Equation 2? Assuming that my derivation to Equation 2 is correct.